Influence of p-n junction mechanism and alumina overlayer on the photocatalytic performance of TiO2 nanotubes. (21st April 2020) - Nair, Sinitha B; John K, Aijo; Joseph, Julie Ann; Babu, Shinto; Shinoj, V K; Remillard, Stephen K; Shaji, Sadasivan; Philip, Rachel Reena
Abstract: Modified hybrid structures of TiO2 nanotubes (TONT), p-Al doped TONT/n-TONT with an additional overlayer of alumina, are constructed to achieve 99.57% photodegradation of the stable organic pollutant methylene blue (MB) within 180 min, a degradation rate 17 times higher than pure TONTs. The anodization at three different temperatures 2, 28 and 40 °C followed by impregnation of Al is used for their preparation. The analyses of structure, chemical composition and morphology are completed using x-ray diffraction, x-ray photoelectron spectroscopy (XPS) and high resolution transmission microscopy, respectively, Rutherford back scattering and field emission scanning electron microscopy confirm the formation of the hybrid structure. This structure exhibits the highest photodegradation rate with TONT based catalysts to date for MB blue, by enhancing the electron—hole separation, the absorption of visible photons and the adsorption sites for the pollutant. The optical data coupled with valence band XPS is used for elucidating the energy band structure of the p-n junctions and to gain insight into the effect of the junction mechanism on photoactivity. The rectification ratios of the impregnated p-n junctions, determined by current—voltage measurements, are found to vary from 10 2 to 10 6 .